A Comparison of Frequency Domain Electro-Magnetometry, Electrical Resistivity Tomography and Borehole Temperatures to Assess the Presence of Ice in a Rock Glacier - Boaga, Jacopo; Phillips, Marcia; Noetzli, Jeannette; Haberkorn, Anna; Kenner, Robert; Bast, Alexander (Frontiers in Earth Science, 2020)
Alpine permafrost is currently warming, leading to changes such as active layer deepening and talik formation. Frequency domain electro-magnetometry (FDEM) measurements were tested at two Alpine permafrost locations on the ice-rich Schafberg rock glacier in the Eastern Swiss Alps as a simple and efficient method to investigate ground characteristics along two transects. The results were compared with electrical resistivity tomography (ERT) and ground temperature data measured in boreholes acquired simultaneously. FDEM provides information on the electrical properties of the ground, which allows to investigate the ground-ice distribution: in our case the device allowed measurements to a depth of around 7 m. In ice-rich permafrost, FDEM can provide an approximation of the active layer thickness and ice-free zones within the permafrost such as intra-permafrost taliks can be identified. This rapidly applicable geophysical method can be used to monitor ground ice distribution easily and efficiently, making it an ideal complement to borehole temperature data, which only provide point information and are costly to install and maintain. At the Schafberg site the three methods FDEM, ERT and borehole temperature measurements provided congruent results regarding active layer depth and the presence of unfrozen zones within the ice-rich permafrost.